The aesthetic dimension: Toward a critique of Marxist aesthetics - Marcuse, Herbert (Boston Beacon Press, 1978)
Developing a concept briefly introduced in 'Counterrevolution and Revolt, ' Marcuse here addresses the shortcomings of Marxist aesthetic theory and explores a dialectical aesthetic in which art functions as the conscience of society. Marcuse argues that art is the only form of expression that can take up where religion and philosophy fail and contends that aesthetics offers the last refuge for two-dimensional criticism in a one-dimensional society.